OP0083 Mir-125a Decreased in Psa Synovium and Peripheral Blood CD14+ Monocytes and Correlates To Joint Angiogenesis. (15th July 2016) - Wade, S.; Connelly, M.; Cregan, S.; Orr, C.; Veale, D.; Fearon, U.
Abstract : Background: Psoriatic Arthritis (PsA) is a chronic immune-mediated inflammatory disease, characterised by proliferation of synovial tissue and destruction of articular cartilage/bone with associated psoriasis. Dysregulated angiogenesis is one of the key early pathogenic processes in PsA. Monocyte subpopulations are increasingly recognized contributors to angiogenesis. Circulating monocytes can differentiate into tissue resident macrophages, monocyte derived dendritic cells and osteoclasts, which orchestrate both pro-inflammatory and pro-angiogenic signalling. These processes may be governed by microRNA (miRNA), a class of evolutionary conserved short non-coding RNAs which function as post-transcriptional repressors of gene expression. On such miRNA is miR-125a-5p, which in cancer, has been previously associated with altered angiogenesis, invasion and migration. Objectives: To examine the expression and angiogenic associations of miR-125a-5p in PsA. Methods: Synovial tissue biopsies were obtained from patients with PsA and osteoarthritis (OA). In parallel, CD14+ monocytes and CD3+ T cells were isolated from peripheral blood mononuclear cells. MiR-125a-5p levels were analysed by real-time PCR. To examine possible factors involved in regulating miR-125a-5p expression in endothelial cells, microvascular endothelial cells (HMVEC) were cultured with candidate pro-inflammatory stimuli including; TLR ligands (PAM, PolyIC, LPS), pro-inflammatory cytokines (TNFa, IL-1b, IL-17) and growth factors (VEGF, Ang2). Matrigel tube formation assays were performed with pre- and anti- 125a treated HMVEC to elucidate angiogenic function. Immunoistochemical analysis of synovial vasculature was performed using factor VIII (DAKO).Cliical markers assertained at the time of arthroscopy, includding synovitis and vascularity were correlated with synovial miRNA expression. Results: Expression of miR-125a-5p was significantly decreased in PsA synovial biopsies (n=8) compared to OA (n=4) (p<0.05). CD14+ peripheral blood monocytes showed a significant decrease in miR-125a-5p compared to whole PBMC (p<0.05). No difference was observed for CD3+ T cells. Anti-125a-5p treated HMVEC displayed increased tube formations. Angiogenic growth factor, Ang2, induced miR-125a-5p in HMVEC (p<0.05). Lower synovial expression of miR-125a-5p displayed a higher degree of factor VIII staining compared to patients with higher miR-125a-5p expression. This was further demonstrated in representative arthroscopic images. Conclusions: Our data demonstrates decreased expression of miR-125a in the joint and peripheral CD14+ monocytes in PsA patients. MiR-125a expression was associated with joint vascularity, a hallmark of PsA, suggesting its important role in mediating key pro-angiogenic and thereby pro-inflammatory mechanisms in the synovium. Correcting these microRNA deficiencies, either by conventional pharmacological agents or as novel targets, may provide a therapeutic benefit, especially in early disease stages. Disclosure of Interest: None declared